Serum vitamin d and risk of prostate cancer in a case-control analysis nested within the european prospective investigation into cancer and nutrition (EPIC) - Travis, R; Crowe, F; Allen, N; Appleby, P; Roddam, A; Tjønneland, A; Olsen, A; Linseisen, J; Kaaks, R; Boeing, H; Kröger, J; Trichopoulou, A; et al. (2009)
Results from the majority of studies show little association between circulating concentrations of vitamin D and prostate cancer risk, a finding that has not been demonstrated in a wider European population, however. The authors examined whether vitamin D concentrations were associated with prostate cancer risk in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (1994-2000). Serum concentrations of 25-hydroxyvitamin D were measured in 652 prostate cancer cases matched to 752 controls from 7 European countries after a median follow-up time of 4.1 years. Conditional logistic regression models were used to calculate odds ratios for prostate cancer risk in relation to serum 25-hydroxyvitamin D after standardizing for month of blood collection and adjusting for covariates. No significant association was found between 25-hydroxyvitamin D and risk of prostate cancer (highest vs. lowest quintile: odds ratio=1.28, 95% confidence interval: 0.88, 1.88; P for trend=0.188). Subgroup analyses showed no significant heterogeneity by cancer stage or grade, age at diagnosis, body mass index, time from blood collection to diagnosis, or calcium intake. In summary, the results of this large nested case-control study provide no evidence in support of a protective effect of circulating concentrations of vitamin D on the risk of prostate cancer.